2018
DOI: 10.1039/c8ra02911c
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of tri(2-chloroethyl)phosphate by a microwave enhanced heterogeneous Fenton process using iron oxide containing waste

Abstract: Iron oxide containing waste was first used in the microwave (MW) enhanced heterogeneous Fenton process for removing tri(2-chloroethyl)phosphate (TCEP) in aqueous solution. The operational parameters that affect the removal efficiency were investigated in detail. Comparing with the traditional Fenton-like reaction and heating assisted Fenton-like reaction, the MW enhanced heterogeneous Fenton process displayed superior treatment efficiency. The iron ore tailing can be reused eight times without significant decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…In contrast to microwave irradiation, where efficient heating of all reaction mixtures by direct coupling of microwave energy with formamide was observed, in the conventional heating, the vessel wall was heated first, and consequently, a longer time was required for the uniform heating of the reaction mixture. Another experiment was carried out to evaluate the possibility of generating hydroxyl radicals without iron since it was reported that the formation of “hot spots” or intensive heating in the microwave can promote the generation of • OH. In this case, only traces of the desired product 3a were observed. Finally, when the reaction was performed in the presence of TEMPO, the desired product was not observed, revealing that the reaction takes place through a mechanism involving free-radical intermediates (Scheme B).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to microwave irradiation, where efficient heating of all reaction mixtures by direct coupling of microwave energy with formamide was observed, in the conventional heating, the vessel wall was heated first, and consequently, a longer time was required for the uniform heating of the reaction mixture. Another experiment was carried out to evaluate the possibility of generating hydroxyl radicals without iron since it was reported that the formation of “hot spots” or intensive heating in the microwave can promote the generation of • OH. In this case, only traces of the desired product 3a were observed. Finally, when the reaction was performed in the presence of TEMPO, the desired product was not observed, revealing that the reaction takes place through a mechanism involving free-radical intermediates (Scheme B).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the left part of have been all detected by experimental techniques (Du et al 2018, Liu et al 2018b, Ye et al 2017, indicating the stable state of these species, with relatively lower Gibbs energy. Since the hydrogen abstraction was energetically more favorable than the •OH attack mechanism, it is surprising to detect both Ma2 and Mb2 as the products.…”
Section: M11mentioning
confidence: 88%
“…H2O2 + O2 Unfortunately only limited theoretical investigations on the mechanism of detailed degradation have been reported compare to the extensive technical and applied studies (Li et al 2017, Luo et al 2018, Zhou et al 2018). Du et al 2018, Liu et al 2018b, Ye et al 2017). These studies indicated two possible pathways for the initial step of TCEP degradation, namely the hydrogen abstraction initiated pathway (HAP) and the •OH attack initiated pathway (RAP), as illustrated in Figure 1.…”
Section: Aopsmentioning
confidence: 99%
See 2 more Smart Citations